Trade unions in Canada, 1812-1902 - Forsey, Eugene A. (Eugene Alfred), 1904-1991 (Heritage., 1982)
Dr Forsey traces the evolutions of trade unions in the early years and presents an important archival foundation for the study of Canadian labour.